Lasers : Development and study of high-power quantum-cascade lasers emitting at 4.5 – 4.6 μm. (30th November 2020) - Dudelev, V V; Mikhailov, D A; Babichev, A V; Savchenko, G M; Losev, S N; Kognovitskaya, E A; Lyutetskii, A V; Slipchenko, S O; Pikhtin, N A; Gladyshev, A G; Denisov, D V; Novikov, I I; et al.
Abstract: Quantum-cascade room-temperature 4.5 – 4.6 μm lasers with different numbers of quantum cascades are developed and studied. It is shown that losses at the metallised sidewalls of the ridge waveguide considerably increase the threshold current density. It is demonstrated that the current density needed to overcome the internal and outcoupling losses in lasers with 30 quantum cascades is an order of magnitude lower than in lasers with 15 quantum cascades.